X-ray Diffraction of Functional Materials - Cornelius, Thomas Walter; Grigorian, Souren (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Demand for advanced X-ray scattering techniques has increased tremendously in recent years with the development of new functional materials. These characterizations have a huge impact on evaluating the microstructure and structure-property relation in functional materials. Thanks to its non-destructive character and adaptability to various environments, the X-ray is a powerful tool, being irreplaceable for novel in situ and operando studies. This book is dedicated to the latest advances in X-ray diffraction using both synchrotron radiation as well as laboratory sources for analyzing the microstructure and morphology in a broad range (organic, inorganic, hybrid, etc.) of functional materials.